2016
DOI: 10.1111/1750-3841.13571
|View full text |Cite
|
Sign up to set email alerts
|

Foam‐Mat Freeze‐Drying of Bifidobacterium longum RO175: Viability and Refrigerated Storage Stability

Abstract: Foaming as a pretreatment was used prior to freeze-drying of Bifidobacterium longum RO175 to investigate the potential acceleration of the drying rate and increase in microorganism viability after the process. A study on storage of foamed and nonfoamed freeze-dried products at 4 °C completed this study. B. longum RO175 in foamed medium could be freeze-dried in 1/7 to 1/4 of the time required for nonfoamed suspensions. In addition, foamed suspensions presented higher viability immediately after freeze-drying (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The suggested method, in turn, allows facilitated diffusion of water molecules and sublimation of ice crystals without damaging the structural integrity of the scaffold. Indeed, the trapped bubbles not only reduce the diffusion resistance compared to condensed phase, but also provide a high surface area for mass transfer, ultimately improving the drying rate and quality 35 . Using this strategy, the deformation could be avoided and the shrinkage reduced to less than 5%, as pointed out in the “Results” section.…”
Section: Discussionmentioning
confidence: 99%
“…The suggested method, in turn, allows facilitated diffusion of water molecules and sublimation of ice crystals without damaging the structural integrity of the scaffold. Indeed, the trapped bubbles not only reduce the diffusion resistance compared to condensed phase, but also provide a high surface area for mass transfer, ultimately improving the drying rate and quality 35 . Using this strategy, the deformation could be avoided and the shrinkage reduced to less than 5%, as pointed out in the “Results” section.…”
Section: Discussionmentioning
confidence: 99%
“…Physicochemical properties of the control and the foam-mat freeze-dried pandan powder during storage time at 4 and 37ºC. F-EW = foam-mat with egg white protein, F-NaCn = foam-mat with sodium caseinate, and F-Mix = foam-mat with the mixture of egg white protein, sodium caseinate, and METHOCEL Izquierdo-Lopez et al (2016) reported the disadvantages of F-FD, mainly due to the porous foam structure and high hygroscopicity of F-FD samples which allow oxygen and moisture to become attached to samples during storage in a refrigerator. The porous structure of FDPP or F-FDPPs allows moisture and oxygen to react more easily with the samples, whereas foaming agents (EW, NaCn, and their mixture with METHOCEL) might provide a film barrier surrounding the particles of pandan powder, which could retard moisture adsorption and oxygen exposure.…”
Section: F I G U R Ementioning
confidence: 99%
“…The porosity of freeze-dried products allows water to adsorb rapidly, thus enhancing high solubility as well as maintaining the original color pigment and fragrant compound. However, the porosity and hygroscopicity of the end product may lead to an increase in oxidation reactions during utilization and storage and destabilize the powder ingredients (Izquierdo-Lopez, Goulet, & Ratti, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the primary disadvantage of this procedure is the duration of time required for drying. To shorten the freeze‐drying time, foaming is used prior to the dying process (Izquierdo‐López et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%